In Operando XANES Imaging of High Capacity Intermetallic Anodes for Lithium Ion Batteries. Issue 4 (4th March 2020) - Gonzalez Malabet, Hernando J.; Juarez Robles, Daniel; de Andrade, Vincent; Mukherjee, Partha P.; Nelson, George J.
Abstract : In operando 2D X-ray absorption near edge structure (XANES) imaging was performed near the Cu K-edge during cycling of Cu6 Sn5 composite anodes for lithium ion batteries. Galvanostatic lithiation and delithiation with intermittent constant voltage holds near reaction plateaus show evolution of absorption spectra for active material particles. XANES spectra obtained from images taken during cycling were compared to standard spectra for Cu, Cu6 Sn5, and Li2 CuSn. Chemical composition was assessed for Cu-containing phases. Distinct Cu, Cu6 Sn5, and Li2 CuSn regions were identified for each voltage plateau. Mechanical degradation, electrode particle fracture and expansion were observed during delithiation. Movement of particles during cycling suggests that expansion also impacts the supporting secondary phases and the transport networks therein. These results demonstrate that spectroscopic X-ray imaging methods can clearly distinguish chemically distinct phases in alloy electrodes and have the versatility to observe the evolution of these phases during lithiation and delithiation.